Are children with disabilities in school and learning? Evidence from a household survey in rural Punjab, Pakistan. Issue 2 (17th February 2022) - Malik, Rabea; Raza, Fizza; Rose, Pauline; Singal, Nidhi
ABSTRACT: Invisibility of children with disabilities in data on educational access and learning is a key policy challenge for tracking progress towards the Sustainable Development Goals. In this article, we report findings from a household survey undertaken in rural Punjab, Pakistan. These data enable us to identify the extent to which children with disabilities are in school and learning the basics in literacy and numeracy. We find that, perhaps contrary to expectations, many of these children in this context are in mainstream (government and private) schools, although their chances of being in school are lower than their peers. We further find that overall levels of literacy and numeracy are low, even more so for children with disabilities. Our findings corroborate recent research from other countries. The paper highlights important lessons for the policy which are of relevance to other low-income contexts.